Photo-synaptic properties of CH3NH3Pb1-xMnxBr2x+1 hybrid perovskite thin film-based artificial synapse. Issue 7 (1st April 2023) - Jeon, Yu-Rim; Lee, Dohee; Cho, Han Bin; Ku, Boncheol; Im, Won Bin; Choi, Changhwan
Abstract: With the increasing demands on unstructured data processing, a system emulating the human nervous system has garnered great attention as an alternative to the von-Neumann architecture due to low power consumption and parallel data processing. To realize the neuromorphic computing, the artificial electronic synapse, neuron device and architecture have been investigated using various materials and devices. In this regard, in addition to electrical-responsive synaptic devices, photoresponsive synapse devices are attracting attention due to photoresponse with high bandwidth, low power consumption, and low current crosstalk. Espicially, the organic-inorganic hybrid halide perovskites (OIHPs) are promising materials for photodevices due to broad optical absorption, low exciton binding energy, fast charge transport properties, and tunable bandgap. The OIHPs have been implemented to demonstrate the photo-stimulated synaptic functions, however, most OIHPs contain toxic lead cations, limiting their widespread application. In this study, we investigated the light-stimulated photosynaptic characteristics based on OIHPs synthesized with Mn 2+ (CH3 NH3 Pb1-x Mnx Br2x+1 ) that could substitute non-desirable Pb-based perovskite. The Mn 2+ -based OIHPs photosynapstor successfully emulated the essential synaptic characteristics including excitatory post-synaptic current, pulse-paired facilitation, post-tetanic potentiation, transition from short-term plasticity to long-term plasticity, forgetting curve, and spike-timing dependent plasticity.